2015
DOI: 10.1016/j.ijimpeng.2014.12.005
|View full text |Cite
|
Sign up to set email alerts
|

Low-velocity impact on multi-layered dual-phase steel plates

Abstract: In this paper an experimental program investigating the behavior of monolithic and multi-layered configurations of 0.8 mm and 1.8 mm medium-strength steel plates is presented. We have considered impacts by blunt-ended and ogival-ended impactors in the low-velocity regime (≤ 16 m/s). Experimental outputs include measurements of force and velocity, and deformation fields. Force and velocity readings were provided by a strain-gauge instrumented striker, while digital image correlation was used to obtain the displ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Extensive research has been conducted over the last decades on unstiffened plates subjected to low-velocity impact loading, e.g. [5][6][7][8][9][10]. The effects of the boundary conditions, the shape of the indenter, the plate material and the velocity and mass of the indenter have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Extensive research has been conducted over the last decades on unstiffened plates subjected to low-velocity impact loading, e.g. [5][6][7][8][9][10]. The effects of the boundary conditions, the shape of the indenter, the plate material and the velocity and mass of the indenter have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Charpy test is performed on notched samples, so deformation process is not relevant to the scenario, where automobile components are confronted during crash accidents. There have also been studies focused on impact performance of thin-walled [43][44][45][46][47] and flat sheet [48,49] specimens. Thin-walled columns composed of various cross-section shape and having various size were examined due to their similarity with automobile mid-rails.…”
Section: Impact Resistancementioning
confidence: 99%
“…Digital image correlation (DIC) technique revealed that the plates' resistance against perforation is closely connected with the shape of the impactor (e.g. blunt-ended or ogival-ended) [48]. Another successive study completed by that team on single DP 600 sheet demonstrated significant effect of strain rate and steel grade on the strain distribution during impact deformation [49].…”
Section: Impact Resistancementioning
confidence: 99%
“…The effects of structural parameters (e.g., the number of layers [ 2 , 3 , 4 , 5 , 6 , 7 , 8 , 9 ] and layer spacing [ 5 , 10 , 11 , 12 , 13 ]) on the ballistic performance of laminated composite armor have been extensively investigated. Additionally, laminated metal armor plates consisting of several kinds of metal layers have been further studied.…”
Section: Introductionmentioning
confidence: 99%